Some observations on the publication of articles in Medicine - Gómez Almaguer, David (UANL. Facultad de Medicina, 2015)
The University is not only a school for adults, but it plays a major role in the search of new knowledge, in other words, research. In addition to assisting patients, teaching colleagues and students --- undergraduates as well as postgraduates --- it is important to highlight the need and duty of doctors to be involved in research. This does not necessarily require a great set of skills or special knowledge; it can be as simple as to cooperate in a workgroup that searches for new knowledge of a specific disease, or more complex activities, like designing and implementing a prospective/comparative study in search of new evidence and different paths than those previously established.